2013
DOI: 10.1007/s12029-013-9552-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MT2 Receptor in Patients with Gastric Adenocarcinoma and its Relationship with Clinicopathological Features

Abstract: According to our results, it is concluded that for the first time, the expression of MT2 receptor in gastric adenocarcinoma tissues which was in parallel with breast and colon cancer studies and high expression of this receptor in the marginal tissues indicate refractory mechanism which shows the defending role of melatonin in the GI system. Our experiments has not shown any relationship between MT2 receptor expression and grade and clinicopathological features of gastric tumor, so we cannot conclude any relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…The demographic and clinical features of the TCGA patients were summarized according to synthesis/metabolism subgroups in Table S2. Consistent with previous observations, 12,22,23 elderly patients tended to have lower melatonin synthesis/metabolism Index, with significant differences observed in BRCA, LIHC, LUAD, LUSC, PRAD, and SKCM; the high-Index subgroup also tended to have a lower proportion of patients with latestage disease, with significant differences observed in CESC, COAD, HNCS, KIRC, SKCM, and THCA.…”
Section: Characteristics Of the Melatonergic Microenvironment Acrossupporting
confidence: 89%
“…The demographic and clinical features of the TCGA patients were summarized according to synthesis/metabolism subgroups in Table S2. Consistent with previous observations, 12,22,23 elderly patients tended to have lower melatonin synthesis/metabolism Index, with significant differences observed in BRCA, LIHC, LUAD, LUSC, PRAD, and SKCM; the high-Index subgroup also tended to have a lower proportion of patients with latestage disease, with significant differences observed in CESC, COAD, HNCS, KIRC, SKCM, and THCA.…”
Section: Characteristics Of the Melatonergic Microenvironment Acrossupporting
confidence: 89%
“…Previous studies have reported that melatonin suppresses the proliferation of several cancer cells and can be viewed as an anti-mitogen [14, 89, 90]. Proliferating-cell nuclear antigen (PCNA) is a molecular marker for proliferation because of its role in cell division; the inhibition of PCNA is considered to be a viable anticancer strategy [91].…”
Section: Effect Of Melatonin On Nsclc Cell Proliferationmentioning
confidence: 99%
“…Uncontrolled proliferation, which is a significant feature of malignant tumors, leads to tumor progression. Previous studies have found that melatonin inhibits cancer proliferation in many cases and can be viewed as an antimitogen . Using a gastric adenocarcinoma cell line, Zhang et al.…”
Section: Effect Of Melatonin On Gastrointestinal Cancer Cell Prolifermentioning
confidence: 99%
“…The incidence of gastrointestinal cancer is increasing worldwide and has caused a heavy health burden on society . Gastric cancer accounts for 8% of the total cancer cases and 10% of total cancer deaths worldwide .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation